Uso de lipossomas com angiotensina-(1-7) para o tratamento de acidente vascular encefálico - Lorena Figueiredo Fernandes (2022)
Stroke is one of the leading causes of death and serious long-term disability worldwide. The only therapeutic agent available is tissue-type plasminogen activator (t-PA), however the number of potential patients is limited because of its side effects and narrow therapeutic window. Thrombectomy is another treatment option providing the surgical removal of the brain clot. Angiotensin-(1-7) [Ang-(1-7)], an endogenous peptide from the renin-angiotensin system, has shown neuroprotective effects in models of in vitro and in vivo ischemia. Ang-(1-7) is rapidly metabolized and to overcome this issue, liposome nanoparticle encapsulation is a valuable approach to prevent degradation of the peptide. Liposomes are vesicles consisting of one or more lipid bilayers surrounding an aqueous compartment. Liposomes are biodegradable, biocompatible, and are able to increase drug efficacy in models of stroke, therefore the use of liposomes as Ang-(1-7) carriers to the Central Nervous System is an asset for ischemic stroke therapy. In this study, Ang-(1-7) encapsulated liposomes were synthesized for the stroke treatment. CD1 mice underwent temporary middle cerebral artery occlusion (MCAO) and immediately or 48h after reperfusion the treatments were intravenously injected. CD1 were also evaluated through a neurological score for functional analyses. The MCAO groups treated immediately after the surgery were euthanized 24h after the surgery and their brains were removed for stroke infarct volume quantification and immunofluorescence. Besides these groups, another group of animals also received treatment immediately or 48h after surgery and were maintained for 7 days. Infarct volume in the brains was measured by magnetic resonance image and the brains were removed for biochemistry analyses. Overwall, the results showed that liposomes were able to increase Ang-(1-7) efficacy when administered immediately or 48 after ischemia. Ang-(1-7) liposomes decreased de infarct volume and improved the animal's function using a smaller dose of Ang-(1-7). Moreover, we also suggested liposome interaction with brain endothelial cells and Ang-(1-7) release in the BBB and also in brain parenchyma explaining its neuroprotective effect. Therefore, the therapeutic strategy suggested in this work presents high potential for stroke treatment. Keywords: Stroke; liposome; angiotensin-(1-7); nanoparticles; ischemia; blood brain barrier.